2020
DOI: 10.1186/s12885-020-07415-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of selected markers of angiogenesis, inflammation, insulin resistance and obesity in type 1 endometrial cancer

Abstract: Background It is a well-known fact show that the risk of developing endometrial cancer (type 1 EC) is strongly associated with obesity. In this study, selected markers, such as obesity, insulin resistance, angiogenesis and inflammation markers related to EC type 1 progression and patients’ survival data were analyzed. Methods To measure levels of adiponectin, C-reactive protein (CRP), vascular endothelial growth factor-A (VEGF-A), an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 49 publications
(66 reference statements)
1
20
0
Order By: Relevance
“…To date, only two studies have examined the relationship between insulin resistance and endometrial cancer survival and did not observe associations between presurgical serum concentrations of insulin and recurrence 18 or overall survival. 19 In cohorts of female breast cancer survivors with assessments of biomarkers up to 1 year postsurgery, higher levels of fasting insulin, compared to lower levels, have been associated with increased recurrences, 29 , 30 , 31 cancer‐specific deaths, 32 and all‐cause mortality. 30 Conversely, high versus low levels of fasting glucose have not been associated with recurrence in postmenopausal women previously operate on for breast cancer (HR = 2.42; 95% CI = 0.90–6.53) 29 or with progression‐free survival in female breast cancer survivors assessed prior to receiving any treatment (HR = 0.82; 95% CI = 0.44–1.51).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, only two studies have examined the relationship between insulin resistance and endometrial cancer survival and did not observe associations between presurgical serum concentrations of insulin and recurrence 18 or overall survival. 19 In cohorts of female breast cancer survivors with assessments of biomarkers up to 1 year postsurgery, higher levels of fasting insulin, compared to lower levels, have been associated with increased recurrences, 29 , 30 , 31 cancer‐specific deaths, 32 and all‐cause mortality. 30 Conversely, high versus low levels of fasting glucose have not been associated with recurrence in postmenopausal women previously operate on for breast cancer (HR = 2.42; 95% CI = 0.90–6.53) 29 or with progression‐free survival in female breast cancer survivors assessed prior to receiving any treatment (HR = 0.82; 95% CI = 0.44–1.51).…”
Section: Discussionmentioning
confidence: 99%
“…Only one study to date has examined the relationship between adipokines (leptin and adiponectin) and endometrial cancer survival and did not observe an association between adiponectin levels and overall survival in women with type 1 endometrial cancer. 19 In breast cancer cohorts, higher levels of adiponectin measured prior to surgery 37 , 38 , 39 and approximately 24 months post‐diagnosis 33 have been associated with better prognosis; however, no associations have been found for leptin. 30 , 37 , 38 , 40 In the current study, higher levels of presurgical adiponectin were associated with improved survival outcomes; however, no associations were found for adiponectin measured postsurgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic inflammation plays a critical role in promoting the progression and metastasis of many cancers ( 20 23 ), and was shown to be associated with the development, progression, and metastasis of cervical cancer ( 24 ). We therefore examined pre-NACT treatment peripheral blood-related inflammatory marker levels in patients with LACC, and the results were consistent with previous findings ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Terlikowska et al found that in EC type 1 patients, serum Ang-2 levels increased with the depth of myometrial infiltration, lymphovascular infiltration, and age and were highest in patients in FIGO stage III–IV. This suggests a key role of Ang-2 in tumor development and metastasis [ 53 ].…”
Section: Angiogenic Diagnostic and Therapeutic Biomarkersmentioning
confidence: 99%